Developing Activities to Promote the Quality of Life for the Elderly. A Case Study of the Phron Subdistrict Administrative Organization, Mueang Yala District, Yala Province - เจะเล๊าะ, ฟิกรี; หนิโซ๊ะ, นิสูฮัยมินทร์; แวหะมะ, อาพาลา; สุขเสนีย์, คมวิทย์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research article has a purpose 1) to study the model for developing activities to improve the quality of life of the elderly in the community context of the local administrative organization of Tambon Pho, Mueang Yala District, Yala Province, and 2) to propose guidelines for developing activities to improve the quality of life of the elderly in the community of Tambon Pho, Mueang Yala District, Yala Province. The research conducted in the area of the local administrative organization of Tambon Pho. The target group consisted of 16 people, including 12 elderly people, 1 staff member, 1 mayor, 1 community development worker, and 1 professional nurse involved in the care of the elderly. The research results found that (1) there are 5 aspects of activity development that affect the quality of life of the elderly: 1) learning and self-development activities, 2) physical exercise activities, 3) social development activities, 4) activities promoting knowledge of media and technology, and 5) religious activities. Appropriate activities help promote physical health, mental health, social participation, and self-esteem of the elderly. Local administrative organizations have an important role in providing budget support, creating an environment conducive to participation in activities, and promoting community participation, which will lead to the sustainable development of the quality of life of the elderly in the long term.